Simplify:
$(5x + 3) (x - 1) (3x - 2)$

AcademicMathematicsNCERTClass 8

Given:

$(5x + 3) (x - 1) (3x - 2)$

To do:

We have to simplify the given expression.

Solution:

$(5x + 3) (x - 1) (3x - 2) = (5x + 3) [x(3x - 2) -1 (3x - 2)]$

$= (5x + 3) [3x^2- 2x - 3x + 2]$

$= (5x + 3) [3x^2 -5x + 2]$

$= 5x (3x^2 - 5x + 2) + 3 (3x^2 - 5x + 2)$

$= 5x(3x^2) - 5x(5x) + 5x(2)+ 3 (3x^2) + 3 (-5x) + 3(2)$

$= 15x^3 - 25x^2 + 10x + 9x^2 - 15x + 6$

$= 15x^3 - 25x^2 + 9x^2 + 10x - 15x + 6$

$= 15x^3 - 16x^2 - 5x + 6$

raja
Updated on 10-Oct-2022 13:19:30

Advertisements